The development of urbanization processes in the Republic of Kazakhstan and abroad: a comparative analysis - Akhmetova, А.S.; Nakipova, G.N.; Turgel, I.D.; Mambetova, S.Sh. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the study is a comparative analysis of the processes of urbanization development in Kazakhstan and in Russia, covering the chronological framework of almost a century period. Methods: concretization and abstraction; retrospective analysis and classification; comparative analysis; descriptive method; statistical methods and methods of scientific analysis and synthesis. Findings: The key findings of the study are summarized in the following conclusions: 1) The special demographic structure of the 1980s was reinforced by the economic restructuring of the 1990s and gave rise to probably the most important problem of the 21st century in Russia and the countries of the former USSR: demographic decline and urban population decline. 2) At present, the development of former socialist cities is largely determined by market forces and democratically elected governments. However, they are also not fully developed capitalist cities. 3) The main similarity between the urbanization of Russia and Kazakhstan is the gap between the most developed major cities of federal and republican significance (Moscow and St. Petersburg, Almaty and Astana) and lagging medium and small cities. 4) In Russia and Kazakhstan, medium and small towns are often characterized by specialized and less diversified economies. Many medium-sized cities are having a hard time adjusting to the slowdown in heavy production and the modernization of the local economy, which leads to problems attracting investment. Conclusions: The development of medium-sized and small cities in Russia and Kazakhstan faces the main problems: lack of financing and/or inefficient use; barriers to decentralization; insufficiently effective regulatory framework and lack of standards or their ineffective implementation regarding sustainable and environmentally friendly development.